Gender-specific insights into adherence to Mediterranean diet and lifestyle: analysis of 4,000 responses from the MEDIET4ALL project - Boujelbane, Mohamed Ali; Ammar, Achraf; Salem, Atef; Kerkeni, Mohamed; Trabelsi, Khaled; Bouaziz, Bassem; Masmoudi, Liwa; Heydenreich, Juliane; Schallhorn, Christiana; Müller, Gabriel; Uyar, Ayse Merve; Ghazzawi, Hadeel Ali; et al. (Frontiers in Nutrition, 2025)
BackgroundThe Mediterranean Diet (MedDiet) is widely recognized for its health benefits, though adherence varies across populations and is influenced by multiple lifestyle and demographic factors. This study examined MedDiet adherence patterns and their associations with lifestyle behaviors, with particular attention to gender differences in a large, multinational cohort.MethodsData were obtained via the MEDIET4ALL survey, an international cross-sectional study that included 4,010 participants (mean age: 36.04 ± 15.06 years; 59.5% female) across 10 countries. The evaluation of adherence to the MedDiet was conducted using the MedLife Index, a validated tool that assesses adherence to MedDiet patterns and lifestyle behaviors through three blocks: Mediterranean food consumption, MedDiet habits, and lifestyle behaviors. Additionally, validated instruments were used to measure associated factors, including perceived barriers to adherence, physical activity, sleep quality and disturbances, mental health, life satisfaction, social participation, and technology use behaviors.ResultsWhile total Mediterranean lifestyle (MedLife) scores showed no significant gender differences, women demonstrated better adherence to food consumption components (p < 0.001), while men showed greater physical activity and social participation. Women reported poorer sleep metrics (efficiency, latency, duration) and higher insomnia severity (all p < 0.05). Psychological distress was more prevalent among women, who also expressed greater needs for psychosocial and nutritional support (p < 0.001). The MedLifeMEDLIFE Index showed significant positive correlations with physical activity (r = 0.298), social participation (r = 0.227), and sleep satisfaction (r = 0.181), and negative correlations with mental health measures (insomnia: r = –0.137; depression: r = –0.115; stress: r = –0.089; anxiety: r = –0.076; all p < 0.001).ConclusionOur findings reveal distinct gender-specific patterns in MedDiet adherence and associated lifestyle factors. These results underscore the need for differentiated public health approaches that address the unique behavioral and psychosocial needs of men and women to promote MedLife adoption.